Effect of Incorporation of Finger Millet(ELEUSINE CORACANA) as a Thickening Agent in chicken Soup - R. Abinayaselvi; D. Santhi; A. Kalaikannan; K. Nandhini (Indian Journal of Veterinary and Animal Sciences Research, 2023)
A study was conducted to optimize the level of finger millet (Eleusine coracana) powder as a thickening agent in the chicken soup prepared with no added oil. Whole finger millet (FM) was powdered finely and used as thickening agent in chicken soup at 0 (control) 5(FM5), 10(FM10) and 15(FM15) parts levels. The pH significantly decreased with increase in the finger millet level where it was highest in control and lowest in FM15. In the sensory evaluation, appearance, flavour and mouth feel scores significantly decreased with increase in finger millet level. The consistency scores were significantly higher for the treatments with finger millet compared to control. The overall acceptability scores were comparable among the control, FM5 and FM10 treatments and significantly lower for FM15. Hence, from this study, it can be concluded that finger millet might be efficiently utilized as a thickening agent in chicken soup up to 10 parts level, which would fortify the nutritive value.